Analisis Metode Just In Time (JIT) Terhadap Efisiensi Biaya Persediaan Suction Tube di PT> Rama Mulia Sentosa - Rengga Purawa; Muhammad Ali Akbar; Bintang Nidia Kusuma (Jurnal Teknologika, 2026)
This study analyzes the application of the Just In Time (JIT) method toward inventory cost efficiency of suction tubes at PT. Rama Mulia Sentosa, an industrial component distributor in Purwakarta. The main problem faced is high inventory costs due to excessively frequent ordering with small quantities, causing waste in storage costs and trapped working capital. This study aims to analyze inventory management conditions before and after JIT implementation, as well as to determine the effectiveness of the method. Suction tube inventory data for January–December 2025 was processed using three approaches: conventional company policy, Economic Order Quantity (EOQ) method, and Just In Time (JIT) method. The calculation results show that the JIT method produces the lowest total inventory cost of Rp 599,833.31 per year, compared to EOQ at Rp 1,469,285.54 and conventional policy at Rp 7,266,922.75. JIT implementation successfully reduced inventory costs by 91.75% compared to the conventional system, with ordering frequency reduced from 48 to 1 time per year. With an average supplier lead time of 5–6 days, the JIT method is considered highly feasible to be implemented at PT. Rama Mulia Sentosa.